Fractured Inferior Pubic Ramus with Ipsilateral Total Hip Replacement: A Case Report and Review of the Literature - Radha, Sarkhell (Hindawi Publishing Corporation, 2013)
Pubic rami fractures are common. They are associated with significant morbidity and mortality. These fractures are usually classified as stable injuries and traditionally receive limited orthopaedic input. Management typically involves hospital admission and early input from physiotherapists and occupational therapists. Early mobilisation is advocated as a central part of managing these patients, with emphasis on secondary prevention. We report a case diagnosed as minimally displaced inferior pubic ramus fracture in a patient with an ipsilateral total hip replacement (THR). The patient was mobilised early and despite analgesia continued to complain of groin pain. Repeat radiographs showed a fracture of the acetabulum with displacement of the acetabular component of the hip replacement. We advocate early orthopaedic input for all pubic rami fractures, particularly in patients with hip arthroplasty, and thorough investigation including a CT scan of the pelvis to exclude acetabular extension prior to mobilisation.